2021
DOI: 10.5435/jaaos-d-20-00934
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Freestanding Ambulatory Surgery Centers: 5-Year Retrospective Chart Review of 90-Day Postsurgical Outcomes and Health Care Resource Utilization

Abstract: Introduction:Migration of total knee arthroplasty (TKA) procedures from the inpatient setting to outpatient venues, especially freestanding ambulatory surgery centers (ASCs), requires the use of reliable patient selection algorithms and standardized perioperative pathways to facilitate favorable outcomes for patients.Methods:This retrospective chart review included consecutive TKA procedures performed over a 5-year period between January 2014 and January 2019 at 2 freestanding ASCs. The patient selection algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…According to the results of these studies, patients who undergo TJR in a same-day outpatient surgical setting and receive fast-track streamlined postoperative education or use an RMA have lower readmission rates (Bahadori et al, 2020; Berg et al, 2018; Campbell et al, 2019; Dehorney & Ashcraft, 2018; Gabor et al, 2020; Glans et al, 2020; Gruskay et al, 2019; Harris et al, 2021; Hussain et al, 2017; Lyman et al, 2020; Mascioli et al, 2021; Oosterholt et al, 2017; Stauber et al, 2020; Timmers et al, 2019; Zheng et al, 2019). Gabor et al (2020) reported low postoperative complication rates and only 2% of the sampled patients were readmitted to the hospital.…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of these studies, patients who undergo TJR in a same-day outpatient surgical setting and receive fast-track streamlined postoperative education or use an RMA have lower readmission rates (Bahadori et al, 2020; Berg et al, 2018; Campbell et al, 2019; Dehorney & Ashcraft, 2018; Gabor et al, 2020; Glans et al, 2020; Gruskay et al, 2019; Harris et al, 2021; Hussain et al, 2017; Lyman et al, 2020; Mascioli et al, 2021; Oosterholt et al, 2017; Stauber et al, 2020; Timmers et al, 2019; Zheng et al, 2019). Gabor et al (2020) reported low postoperative complication rates and only 2% of the sampled patients were readmitted to the hospital.…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
“…A systematic review has been conducted (Bahadori et al, 2020). The remaining nine articles were observational studies categorized as prospective comparative studies, before-and-after studies, retrospective studies, and case studies (Berg et al, 2018; Dehorney & Ashcraft, 2018; Gabor et al, 2020; Glans et al, 2020; Gruskay et al, 2019; Harris et al, 2021; Lyman et al, 2020; Mascioli et al, 2021; Oosterholt et al, 2017; Zheng et al, 2019).…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
“…Clinically, postoperative morphine consumption at 24 and 48 h was significantly lower in the CoQ10 group when compared to the control and CoQ10 + IPC groups (Median [P25-P75] at 24 h; CoQ10 3.5 [ 1 , 2 , 3 , 4 , 5 , 6 ] vs. placebo 6 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] vs. CoQ10 + IPC 9 [6–13.5] mg, p = 0.037) ( Figure 5 A). In accordance with the cumulative morphine dose, the NRS at 24 h was significantly lower in the CoQ10 group when compared to the placebo and the CoQ10 + IPC groups (Median [P25-P75]; CoQ10 2.5 [ 2 , 3 , 4 ] vs. placebo 5.5 [ 3 , 4 , 5 , 6 ] vs. CoQ10 + IPC 5.5 [ 3 , 4 , 5 , 6 ] mg, p = 0.013) ( Figure 5 B). These results indicated that CoQ10 provided preventive analgesia within the first 48 h after TKA.…”
Section: Resultsmentioning
confidence: 99%
“…Perioperative care of TKA becomes more challenging in patients with increasing age and multiple comorbidities [ 1 , 2 ]. Also, TKA has a trend toward an ambulatory setting [ 3 , 4 ]. Thus, besides a current anesthesia practice, alternative strategies to enhance function at the cellular levels are essential as an adjunct therapy to improve postoperative clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 and 2020 respectively, TKA and THA were removed from the inpatient-only (IPO) list for Medicare reimbursement. This opened the door to Medicare reimbursement for TKA and THA in an ambulatory surgery center (ASC) through the addition of TKA and THA to the ASC covered-procedures list in 2020 and 2021, respectively 10-14 . Because of the transition of TJA to lower-cost settings, cost savings for insurers are expected to be substantial, and this trend will likely continue into the future 15-17 .…”
mentioning
confidence: 99%